Influence of shear reinforcement configurations and special concretes on the performance of exterior slab-column joints under cyclic loading - Suganya, K.N.; Greeshma, S. (Journal of Structural Engineering, 2024)
To develop earthquake-resistant structures, substantial research and the dissemination of design and detailing knowledge are essential for structural elements. The current study involves both numerical and experimental investigations focused on the behavior of external slab-column connections under cyclic loads. Three distinct specimen types were assessed: a Conventional Specimen without shear reinforcement in slab (CS), a specimen featuring shear stud reinforcements arranged in a radial pattern, with forging slag and Styrene Butadiene Rubber (SBR)-modified concrete at the joint (SSR), and with a specimen with steel fiber-reinforced concrete at the joint (SSC) and shear studs. These scaled models (1/4th scale) underwent axial loading applied at the top of the column stub, and cyclic loading to the slab edge. In all axial and cyclic stress scenarios, the models with Slab Shear Reinforcements (SSR and SSC) showed superior resistance to punching shear failure under both axial and cyclic loading conditions. The inclusion of shear stud reinforcements (SSR and SSC) notably enhanced the ductility compared to the CS. Furthermore, the energy dissipation capacity of the specimens was evaluated and compared, with shear reinforcements showing a significant improvement.